The impact of accessibility of mobile devices on the intention to post online reviews - Jeongsoo Han; Mina Jun (European Journal of Management and Business Economics (EJM&BE), 2021)
Purpose - The purpose of this paper is to investigate how the characteristic of mobile devices, particularly high accessibility, influences a consumer's intention to post an online review depending on the valence of consumption experiences. Design/methodology/approach - This paper employs a between-subject design of experimental study based on different scenarios with 378 participants. A pretest is conducted to confirm that participants perceive the experimental scenarios as intended prior to proceeding with the main experimental study. Findings - The authors' experimental analysis shows that the intention to post a review of extreme positive and negative experiences is significantly higher when the level of accessibility for review-posting is high. By contrast, the intention to post a review of neutral consumption experiences is neither higher nor lower regardless of the level of accessibility. Originality/value - The findings of this paper contribute to a better understanding of online reviews by demonstrating how high accessibility for review-posting have differential influences on the intentions to post online reviews depending on the valence of consumer experiences. The findings provide important theoretical and managerial implications.
Keywords: 650; Accessibility; Mobile devices; Online review; Review-posting behavior; Social exchange theory